Activation of Fas by FasL induces apoptosis by a mechanism that cannot be blocked by Bcl-2 or Bcl-x(L) - Huang, David C. S. (The National Academy of Sciences, 1999)
Fas activation triggers apoptosis in many cell types. Studies with anti-Fas antibodies have produced conflicting results on Fas signaling, particularly the role of the Bcl-2 family in this process. Comparison between physiological ligand and anti-Fas antibodies revealed that only extensive Fas aggregation, by membrane bound FasL or aggregated soluble FasL consistently triggered apoptosis, whereas antibodies could act as death agonists or antagonists. Studies on Fas signaling in cell lines and primary cells from transgenic mice revealed that FADD/MORT1 and caspase-8 were required for apoptosis. In contrast, Bcl-2 or Bcl-x(L) did not block FasL-induced apoptosis in lymphocytes or hepatocytes, demonstrating that signaling for cell death induced by Fas and the pathways to apoptosis regulated by the Bcl-2 family are distinct.